Analysis of the Implementation of Head Nurse Clinical Supervision on Improving the Quality of Nursing Services: A Literature Review - Rosana Silalahi; Asnet Leo Bunga (Jurnal Impresi Indonesia, 2025)
Nurses constitute the largest human resource group in hospitals and are the health professionals with the most prolonged direct client interaction. Consequently, the quality of nursing services is a fundamental determinant of overall healthcare quality in hospitals. As the frontline leader in nursing service management, the head nurse plays a critical role in conducting clinical supervision to monitor nurse performance and enhance service quality. This study aimed to analyze the implementation of head nurse clinical supervision for improving nursing care quality through a literature review. Databases including PubMed, Science Direct, EBSCO, J-Stor, and ProQuest were searched, resulting in the extraction of 10 relevant articles. All studies confirmed a significant relationship between effective clinical supervision and improved nursing service quality, as measured through nurse performance. Effective supervision fosters responsibility and motivation among nurses, leading to better execution of nursing care, clinical actions, and discharge planning. The consistent finding across articles underscores that structured supervision models are substantially more effective than non?model approaches. Moreover, nursing service quality can be comprehensively evaluated by examining the entire care process—from patient admission to discharge planning. These results highlight the importance of adopting systematic supervisory frameworks to achieve high?quality nursing outcomes.